2017
DOI: 10.1111/een.12426
|View full text |Cite
|
Sign up to set email alerts
|

Does competition with wind‐pollinated species alter Echium plantagineum's attractiveness to a common pollinator Bombus terrestris?

Abstract: 1. In insect-pollinated plants, pollinator attraction is influenced by flowers (e.g. number, size) and their associated rewards (e.g. pollen, nectar). These traits can depend on plant interactions. Indeed, below-ground competition between plants can lead to a decrease in flower or reward production in insect-pollinated species. 2. Wind-pollinated plants, in particular, which are almost never studied in plant-pollinator networks, can alter insect-pollinated plants' attractiveness through competition for nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…plant probability of displaying flowers, plant floral display size, flower size) distance were negatively influenced by the competition treatment. This has been observed in previous studies, especially at the plant level ( Baude et al 2011 ; Partzsch and Bachmann 2011 ; Flacher et al 2015 , 2017 ) probably through soil resource depletion as floral traits can be sensitive to soil resource availability ( Muñoz et al 2005 ; Burkle and Irwin 2009 ). In contrast, reward traits such as nectar volume and concentration remained constant regardless of the competitive context.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…plant probability of displaying flowers, plant floral display size, flower size) distance were negatively influenced by the competition treatment. This has been observed in previous studies, especially at the plant level ( Baude et al 2011 ; Partzsch and Bachmann 2011 ; Flacher et al 2015 , 2017 ) probably through soil resource depletion as floral traits can be sensitive to soil resource availability ( Muñoz et al 2005 ; Burkle and Irwin 2009 ). In contrast, reward traits such as nectar volume and concentration remained constant regardless of the competitive context.…”
Section: Discussionsupporting
confidence: 72%
“…By measuring plant biomass, we assessed the competition outcome rather than the competition itself ( Trinder et al 2012 ). Nevertheless, Flacher et al (2015 , 2017 ) showed that H. lanatus plants can display a large and dense root system that can lead to a reduction of their neighbour’s biomass. Moreover, plant size and biomass can lead to some advantages especially for the occupation of soil space and nutrient acquisition ( Berntson and Wayne 2000 ; Raynaud and Leadley 2004 ; Gurevitch et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, floral scent is highly sensitive to increased temperature (Farré‐Armengol et al, 2014; Yuan et al, 2009) and drought, with increased emissions under moderate stress (Burkle & Runyon, 2016; Campbell et al, 2019; Glenny et al, 2018). Altered floral attractiveness could therefore affect pollinators' foraging behaviour and resource choices (Flacher et al, 2017, 2020). For instance, herbivore‐induced plant volatiles present in floral scent tend to deter pollinators from floral resources in attacked plants (Hoffmeister & Junker, 2017; Kessler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%